Failure Analysis of Galvanized Iron Pipe at Perumda Tirta Kanjuruhan - Pramita, Cynthia Rosa; Suprapto, Agus; Widyastuti, Ike (Universitas Merdeka Malang, 2023)
The most commonly used type of water pipe is iron pipe or commonly called Galvanized Iron pipe. The disadvantage of GI pipe is that it rusts easily. So it can result in degradation, decreased efficiency and construction, poor water quality, and higher maintenance costs. Water channeled through rusty pipes will pollute the water and adversely affect the health of those who consume it. This study aims to determine the factors causing failures of GI pipe in the distribution pipeline that have failed due to corrosion. The tested pipes is 1/2